Allostatic load and its determinants in a German sample—Results from the Carla cohort - Eric Priedemann; Alexander Kluttig; Frank Bernhard Kraus; Daniel Sedding; Rafael Mikolajczyk; Amand Führer (PLoS ONE, 2025)
Background Allostatic load (AL) is a surrogate of the physiological response to stress and reflects the ‘wear and tear’ on the body. Previous studies indicated that socioeconomic and behavioral determinants influence AL, which in turn is associated with health outcomes. Therefore, AL is increasingly used to operationalize the relationship between social inequality, stress, and health outcomes. This study aimed to investigate associated factors and patterns of AL in the population over a 20-year period using data from the CARLA cohort. Methods The analysis included 473 participants from the CARLA study (Cardiovascular Disease, Living and Ageing in Halle), aged 45–80 years at baseline. From recruitment in 2002 in Halle (Saale), three follow-up examinations took place until 2022. We calculated AL scores as the sum of standardized z-scores for metabolic, immune, cardiovascular, and anthropometric components. Descriptive statistics of AL scores were stratified by sex and age categories. Multiple regression analyses were conducted for the first and third follow-up to assess if there were changes in associations between sociodemographic factors and AL. Results Average AL scores of men decreased, while women’s AL scores returned to baseline levels after an initial decrease observed at the first follow−up. Stratified analyses of AL scores revealed that women in the younger age cohorts had lower mean AL scores at baseline than men (women: −3.47, 95% CI [−4.24; −2.71] vs. men: −1.13, 95% CI [−1.84; −0.42] at age <55). At the same time, women showed higher mean AL scores than men in older age cohorts (women: −0.32, 95% CI [−1.58; 0.95] vs. men: −0.93, 95% CI [−1.99; 0.14] at age 65−<70). Results of multiple regression models indicated lower AL scores for women (β: −1.21, 95% CI [−1.93, −0.49]). Professional status was associated with lower AL scores for men but not for women (β: −1.06, 95% CI [−2.02, −0.11] for men). Further, physical activity was negatively associated with AL scores for the total study sample and for women (β: −0.54, 95% CI [−0.82, −0.26]) for total sample and β: −0.74, 95% CI [−1.17, −0.32] for women). Conclusion Our results highlight the importance of health awareness and physical activity for overall health, assessed by AL. Distinct AL score changes and sex-specific socioeconomic influences offer insights into sex-related patterns of aging. Further research is needed to understand the underlying mechanisms of socioeconomic influences on stress-related aging processes between sexes.